Variable thermoregulation of Late Cretaceous dinosaurs inferred by clumped isotope analysis of fossilized eggshell carbonates. Issue 10 (October 2020) - Laskar, Amzad H.; Mohabey, Dhananjay; Bhattacharya, Sourendra K.; Liang, Mao-Chang
Abstract: The thermal physiology of non-avian dinosaurs, especially the endothermic/ectothermic nature of their metabolism, inferred indirectly using body mass, biophysical modelling, bone histology and growth rate, has long been a matter of debate. Clumped isotope thermometry, based on the thermodynamically driven preference of 13 C- 18 O bond in carbonate minerals of fossilized eggshells, yields temperature of egg formation in the oviduct and can delineate the nature of thermoregulation of some extinct dinosaur taxa. In the present study, the clumped isotope thermometry was applied to the eggshells of a few species of modern birds and reptiles to show that it is possible to obtain the body temperatures of these species in most of the cases. We then used this method to the fossil eggshells of Late Cretaceous sauropods and theropods recovered from western and central India. The estimated body temperatures varied between 29 °C and 46 °C, with an overall average of 37 °C, significantly higher than the environmental temperature (about 25 °C) of this region during the Late Cretaceous. The results also show that the theropod species with low body masses (~800 kg) had high body temperature (~38 °C), while some gigantic (~20000 kg) sauropods had low body temperatures that were comparable to or slightly higher than the environmental temperature. Our analyses suggest that these Late Cretaceous giant species were endowed with a capacity of variable thermoregulation to control their body temperature. Abstract : Earth sciences, Paleobiology, Geochemistry, Dinosaur, Eggshell carbonate, Clumped isotopes, Body temperature, Thermal physiology.